Putative Auditory-Evoked Neurophonic Measurements Using a Novel Signal Processing Technique: A Pilot Case Study - Cook, Alison M.; Allsop, Ashleigh J.; O'Beirne, Greg A. (Frontiers in Neuroscience, 2017)
With changes to cochlear implant candidacy and improvements in surgical technique, there is a need for accurate intraoperative assessment of low-frequency hearing thresholds during cochlear implantation. In electrocochleography, onset compound action potentials (CAPs) typically allow estimation of auditory threshold for frequencies above 1 kHz, but they are less accurate at lower frequencies. Auditory nerve neurophonic (ANN) waveforms, on the other hand, may overcome this limitation by allowing phase-locked neural activity to be tracked during a prolonged low-frequency stimulus rather than just at its onset (Henry, 1995). Lichtenhan et al. (2013) have used their auditory nerve overlapped waveform (ANOW) technique to measure these potentials from the round windows of cats and guinea pigs, and reported that in guinea pigs these potentials originate in the cochlear apex for stimuli below 70 dB SPL (Lichtenhan et al., 2014). Human intraoperative round window neurophonic measurements have been reported by Choudhury et al. (2012). We have done the same in hearing impaired awake participants, and present here the results of a pilot study in which we recorded responses evoked by 360, 525, and 725 Hz tone bursts from the cochlear promontory of one participant. We also present a modification to the existing measurement technique which halves recording time, extracting the auditory neurophonic by recording a single averaged waveform, and then subtracting from it a 180° group-delayed version of itself, rather than using alternating condensation and rarefaction sound stimuli. We cannot conclude that the waveforms we measured were purely neural responses originating from the apex of the cochlea: as with all neurophonic measurement procedures, the neural responses of interest cannot be separated from higher harmonics of the cochlear microphonic without forward masking, regardless of electrode location, stimuli or post-processing algorithm. In conclusion, the extraction of putative neurophonic waveforms can easily be incorporated into existing electrocochleographic measurement paradigms, but at this stage such measurements should be interpreted with caution.